Dielectronic recombination data for dynamic finite-density plasmas - VI. The boron isoelectronic sequence - YUMAK YAHŞİ, AYŞE; ALTUN, ZİKRİ (EDP SCIENCES S A, 2004)
We have calculated dielectronic recombination rate coefficients for 22 ions of the boron isoelectronic sequence, between C+ and Xe49+, within the generalized collisional-radiative framework, as outlined by Badnell et al. (2003). Calculations have been performed from both ground and metastable initial states, in both LS- and intermediate-coupling, allowing for Deltan = 0 and Deltan = 1 core-excitations. Results are presented and discussed for a selection of ions from the sequence. Results which are not presented here can be accessed from the Atomic Data and Analysis Structure (ADAS) database (Summers 2003) or from the Oak Ridge Controlled Fusion Atomic Data Center (http://www-cfadc.phy.ornl.gov). Comparison is made with the results of other existing theoretical calculations.
Keywords: atomic data; atomic processes; plasmas; ELECTRON-ION RECOMBINATION; B-LIKE IONS; ASTROPHYSICALLY ABUNDANT ELEMENTS; RATE COEFFICIENTS; IONIZATION EQUILIBRIUM; CROSS-SECTION; MAGNETIC-FIELDS; FE-XXII; TEMPERATURE; CARBON